Digital Business of the Industry 4.0 Concept in International Economic Relations - SARKISYAN, Zhaklin M. (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
In modern society, digital technologies determine the competitiveness of national socio-economic systems and become the leading drivers of economic growth. Depending on the degree of influence of information progress, the market begins to dictate new trends that affect all business sectors and provide competitive advantages organizations that have time to adapt to new conditions. Competitive advantages of any subjects of economic relations in a market economy, including digital businesses, are provided by a significant increase in profits (more than 26 % for companies with a high share of digitalization), more efficient work of employees, increased profitability, optimization of tangible assets, etc. The methods of strategic, tactical and operational-calendar planning were used to solve the tasks. The influence of digitalization on the emergence of new and changes in existing business models is shown. Affected the prospects for the development of digital technology in the factories.